Inovação no arranjo produtivo local : setor automotivo na região de Caxias do Sul - Ciconet Filho, Isidoro (Universidade do Vale do Rio dos Sinos, 2012)
This thesis investigates the how occurs the interaction for innovation in Local Metal-Mechanical-Automotive Productive Arrangement in the region of Caxias do Sul (RS), from the analysis of New Institutional Economy theoretical framework (COASE, 1937; NORTH, 1990; WILLIAMSON, 1985; NELSON, 2008); Evolutionary Economic Theory or Neo-Schumpeterian (SCHUMPETER, 1950); Innovation Systems (FREEMANN, 1995, EDQUIST 2004, LUNDVALL, 1992), and Local Productive Arrangement (SUZIGAN, W, 2001; SUZIGAN, W.; FURTADO, J.; GARCIA, R. 2007; CASSIOLATO; LASTRES, 1999), having in mind examining the arrangement in the field of innovation study; besides having as a theme limit factors that comprise territorial proximity, the interaction processes among various agents that integrate the local productive system that affect the companies’ competitive and innovative performance on the arrangement under study. For institutionalists, institutional environment is relevant, because economic analysis goes through the study of structures, institutions rule sand behaviors (companies, unions, the State and its agencies). For Evolutionary Economic Theory or Neo-Schumpeterian Theory, economic activity is dynamic, having technology an evolutive and endogenous character to the process of economic development with the business entrepreneur central presence. The approach of National Systems has suggested the systemic character of innovative activity in which knowledge and learning by interaction have been highlighted; additionally provides that regions economic development has been grounded in expanding the physical technologies structures, and expanding social technologies. In Brazil, recent studies on APLs have realized that a conceptual proposal for local innovation systems seems to offer a better chance of understanding the process of innovation, in diversity, consider that exists among different countries and regions, in view of their specific historical processes, and their singular institutional policy designs. This framework is based on some fundamental concepts – learning, interactions, skills, complementarities, selection, dependence of paths, among others, which emphasize regional and local aspects. Therefore, these issues have become relavant to analyze regional development and, more specifically, to evaluate how occurs interaction for innovation in specific environments. On this basis, this thesis seeks to analyze the how occurs interaction for innovation among stakeholders in Local Metal-Mechanical-Automotive Productive Arrangement, in the region of Caxias do sul (RS). So as to achieve the goal, it has been carried out a descriptive research using a survey as a data collection technique. The results have indicated that behavior alternates among stakeholders due to their peculiar characteristics. Interaction for innovation, considering support institutions and services, institutions of influence have indicate (i) a more prominent role of support institutions and services, agents that act on behalf of interaction and are mostly recognized as important by the other agents in the innovation process; (ii) institutions of influence has interacted less intensively, in relation to support institutions and services; (iii) for companies, the results have pointed to an embryonic interaction with institutions, mainly the small and micro companies group, which practically have not acted proactively in search of information and knowledge for innovation with institutions; (iv) the relationship among companies, i.e, among themselves, interaction happens searching information from their customers and users, a practice adopted by large enterprises, and searching information from their suppliers, used by smaller companies. Finishing the study, under the light of Theory on Regional Economy, it can be inferred that APL social bases, constituted by entities that comprise the Board of Directors, must move towards so as to become more effective in their roles as APL promoters and its development.
Keywords: Arranjo produtivo local; Inovação; Interação; Local productive arrangement; Innovation; Interaction; ACCNPQ::Ciências Sociais Aplicadas::Administração